Spectroscopic Studies of the Behavior of Eu3+ on the Luminescence of Cadmium Tellurite Glasses - I. V. García-Amaya; Ma. E. Zayas; J. Alvarado-Rivera; E. Álvarez; S. A. Gallardo-Heredia; G. A. Limón; R. Lozada-Morales; J. Ma. Rincón (Journal of Spectroscopy)
The effect of europium doping on the photoluminescence of ZnO-CdO-TeO2 glasses is analyzed. TeO2-based glasses are of high interest as hosts for laser glasses. The Eu-doped oxide glasses were prepared by the conventional melt-quenching method. Five different concentrations of europium nitrate hexahydrate that varied from 0.3 to 1.5 mol% were used. SEM observations revealed the formation of zinc aluminate spinel and disperse droplets of liquid-liquid phase separation in the glasses. X-Ray diffraction reveals the amorphous structure of the fabricated glasses. FT-IR and Raman spectra show the presence of TeO4 and TeO3+1/TeO3 units that conform with the glass matrix. Raman spectra evidenced a band located at 1556 cm−1 that can be related to interstitial molecular oxygen in the glass matrix. Photoluminescence of the glasses showed light emission due to the following europiumtransitions from its D52, D51, and D50 levels to its F7J manifolds: D52→F70 (468 nm), D52→F72 (490 nm), D52→F73 (511 nm), D51→F71 (536 nm), D51→F72 (554 nm), D50→F70 (579.5 nm), D50→F71 (592 nm), D50→F72 (613 nm), D50→F73 (652 nm), and D50→F74 (490 nm). The estimated decay time, τ, was 0.4 ms for all the glasses.